Republic of Kosovo : Third Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance of Criterion. (IMF Staff Country Reports; Country Report, 2013)
Kosovo's macroeconomic and financial policies have remained broadly on track. Progress continues to be made toward the key objectives, id est, restoring a sustainable fiscal position and sufficient government cash buffers, anchoring fiscal policy, and enhancing the resilience of the financial system. Careful preparation of social spending initiatives and fragile political environment remains key. The policies under the program provide the best safeguard to steer the economy through the period ahead, establish confidence in macroeconomic management, and lay the foundations for robust and balanced growth.